Degradation of Cd, Cu, Fe, Mn, Pb and Zn by Moringa-oleifera, zeolite, ferric-chloride, chitosan and alum in an industrial effluent - Jagaba A.H.; Kutty S.R.M.; Hayder G.; Baloo L.; Ghaleb A.A.S.; Lawal I.M.; Abubakar S.; Al-dhawi B.N.S.; Almahbashi N.M.Y.; Umaru I. (Ain Shams University, 2023)
Aluminum compounds; Chitosan; Chlorination; Chlorine compounds; Coagulation; Effluents; Flocculation; Inductively coupled plasma; Iron compounds; Lead; Mixing; Ostwald ripening; Sewage; Sewage treatment plants; Sulfur compounds; Wastewater treatment; Zeolites; Zinc; Atomic absorption spectrometers; Coagulation flocculation; Constant parameters; Flocculation and sedimentation; Inductively coupled plasma (ICP); Industrial effluent; Metals concentrations; Water and wastewater treatments; Chemical water treatment